Case report: Fecal microbiota transplant for Clostridium difficile infection in a pregnant patient with acute severe ulcerative colitis - Wang, Hanyu; Deng, Feihong; Luo, Min; Wang, Xuehong (Frontiers in Immunology, 2024)
Ulcerative colitis (UC) is a chronic colonic mucosal inflammation characterized by reduced gut microbial diversity. UC patients at pregnancy are prone to suffer from sever disease progression due to the changes of hormone and immune regulation. Fecal Microbiota Transplant(FMT) is a promising therapy for UC and recurrent Clostridium difficile infection (CDI). However, acute severe ulcerative colitis(ASUC) treatment especially in patient at pregnancy is clinical challenging. Herein, we report a 34-year-old pregnant woman who manifested with numerous bloody stool and markedly elevated serological inflammatory indicators, was diagnosed with ASUC and concurrent CDI. She was failed to intravenous injection steroids and anti-TNF-α therapy. Frozen encapsulated FMT therapy was finally performed to this patient with clearly improved symptoms and good condition of delivery without UC flares or complications, markedly increased diversity of the gut microbiota was also showed in this patient after FMT. This report firstly describes FMT might as a safe salvage therapy for the pregnant patient with CDI and ASUC refractory to intravenous steroids and anti-TNF therapy.